KEANEKARAGAMAN PLANKTON DAN HUBUNGANNYA DENGAN KUALITAS AIR SUNGAI SEKITAR PABRIK KELAPA SAWIT (STUDI KASUS DI ASAM-ASAM, JORONG KABUPATEN TANAH LAUT) - Dzikrina, Dhia; Rahman, Mijani; Akbar, Arief R. M.; Yunita, Rizmi (EnviroScienteae, 2023)
The Asam-Asam  River is one of the waters located in Tanah Laut Regency and is in an oil palm plantation area which is very close to the Palm Oil Mill (PKS). The Asam-Asam  River has an important role for the surrounding community who use these waters as a source of water for the community around fishing activities, domestic activities such as washing clothes and supplying water for oil palm plantations. Water from PKS activities is thought to have changed the condition of the waters of the Asam-Asam  river, therefore identification of plankton diversity in the Asam-Asam  River was carried out and data collection of water quality parameters (pH, temperature, DO, BOD, COD, Nitrate and Phosphate) as supporting data for the identification results plankton. This research was conducted in August 2021. Observation points and water sampling were carried out at 2 stations in the Asam-Asam  River. The supporting parameters observed were pH, temperature, DO, BOD, COD, nitrate and phosphate. Station II had the highest abundance of phytoplankton because the presence of the genera Oscillatoria, Tablelaria and Spirogyra was much higher than Station I. In the results of the two observation stations, the class Bacillariophyceae was the most common.